EP.TH.447Simultaneous repair of bilateral Inguinal hernia under Local Anaesthetic - is it feasible?. (28th October 2021) - Athisayaraj, T; Olugbemi, J; Sebastian, B; Coveney, E
Abstract: Introduction: Local Anaesthetic repair of unilateral Inguinal hernia is well reported in the literature, as a safe, well tolerated and effective operation. However, there is not much literature on simultaneous repair of bilateral inguinal hernias under local anaesthetic. We are reporting our experience with simultaneous repair of bilateral inguinal hernias under local anaesthetic. Methods: We did a retrospective analysis of prospectively collected data of patients, who had bilateral inguinal hernia repaired under local anaesthetic over a period of 2009 - 2019, looking at the patient demographics, patient reported pain score, operating time, volume of local anaesthetic used, patient satisfaction and complication rates.All the patients had Lichtenstein's hernioplasty. The LA mixture was made up of 30ml 0.5% Bupivacaine with adrenaline, 20 ml 2% Lignocaine with adrenaline, 50 ml of 0.9% Saline and 6 ml of 8.6% Sodium Bicarbonate. All these surgeries were performed on a day case basis. Results: There were 24 patients, who underwent local anaesthetic repair of bilateral inguinal hernias, 22 Males and 2 Females. Age range was 35 - 81 years. The BMI varied from 18 - 30, with a mean of 24. The average operating time was 66.8 minutes (38 - 120 minutes, median 60 min). The mean pain score was 24, on a 0-100 scale. Patient satisfaction scores varied from 50-100 (Median 90, Mean 88.1) Conclusion: We conclude that successful simultaneous repair of bilateral inguinal hernia under local anaesthetic is feasible, with a low level of patient discomfort, high satisfaction rate and using safe quantities of local anaesthetic